Edukasi dan Simulasi Kesiapsiagaan Bencana Gempa Bumi pada Siswa Mtsn Sumba Timur - Ayu Wahyuni Lestari; Ineke Noviana; Martha Meti Kody (Jurnal Kemitraan Masyarakat, 2024)
Earthquakes are one of the most common and potentially devastating natural disasters, especially in countries located along fault lines. Indonesia, which is located on the Pacific Ring of Fire, often experiences earthquakes. Simulations can improve children's disaster preparedness, provide self-confidence, and foster a sense of responsibility. Community service activities were carried out at MTsN Sumba Timur on September 7, 2024 starting at 08.00 -10.00 WITA. The name of the community empowerment program is Earthquake Disaster Preparedness Education and Simulation for MTsN Sumba Timur Students as a form of community service in the East Sumba NTT region, by providing education and understanding of the dangers of earthquakes and how to prevent accidents due to earthquakes, as well as providing simulations to maximize participants' knowledge. The first stage is a pre-test on disaster mitigation. This aims to determine students' initial understanding of earthquake disaster mitigation. There are eight Guttman scale questions containing "yes" and "no" answer choices with one correct answer. Next is the presentation of material on earthquake disaster mitigation supported by the use of power points and animated videos. The material provided is in the form of a disaster preparedness plan that includes an introduction to the types of earthquakes, the impact of earthquakes, what happens when an earthquake occurs, and the stages of efforts to increase preparedness before an earthquake occurs, when an earthquake occurs. and after an earthquake occurs. Community service activities through Earthquake Disaster Preparedness Education and Simulation for MTsN Sumba Timur Students were carried out well and effectively. The suggestions that can be conveyed are 1. Activities like this should be carried out periodically in different locations but are prone to disasters so that Disaster Preparedness efforts can be felt by the community fairly and evenly. 2. Partnerships with other sciences and sectors so that Disaster Preparedness efforts can be evenly distributed in all aspects of community life towards optimal public health.